Arthroscopic Dorsal Scapular Nerve Decompression for Painful Scapulothoracic Abnormal Motion: Technique and Indications - Ryan Lohre, M.D.; Abdulaziz F. Ahmed, M.D.; Bassem Elhassan, M.D. (Arthroscopy Techniques)
Patients with scapulothoracic abnormal motion can present with debilitating medial scapular border pain. In patients with scapulothoracic abnormal motion and evidence of diffuse medial scapular border pain along the dorsal scapular nerve (DSN) distribution, surgical release of the DSN is indicated. This Technical Note provides an all-arthroscopic approach to thoracic decompression of the DSN.